Repression And Sublimation In Forrest Gump By Winston Groom: A Psychoanalytic Investigation - Friscilla, Okti Dea; Antaridha, Rabbi (LPPM Universitas Dharma Andalas, 2025)
This study examines the main character, Forrest Gump, from Winston Groom’s 1986 novel. Despite being labeled an